2000
DOI: 10.1021/ma000484j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Macromolecular Helicity Induction of a Stereoregular Polyacetylene Bearing a Carboxy Group with Natural Amino Acids in Water

Abstract: Since most important biological events occur in aqueous solution where biopolymers such as proteins and DNA form a characteristic helical conformation, significant attention has recently been paid to developing artificial polymers and oligomers that adopt a onehanded helical conformation in aqueous solution, particularly in light of emerging applications in the biomedical and materials science fields and also for mimicking protein folding. 1 However, most synthetic helical polymers and oligomers prepared so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 30 publications
4
128
0
1
Order By: Relevance
“…In the presence of bases such as NaOH and amines, (4-carboxyphenyl)-acetylene was rapidly and homogeneously polymerized with water-soluble rhodium complexes to yield high molecular weight poly-16 in high yields. 25 The obtained sodium salt of poly-16 also formed a predominantly one-handed helical structure with natural amino acids in water, and the complexes showed an ICD in the UV-visible region. However, this polymer is not sensitive to amino acids and other important chiral biomolecules in the fields of biology and medicine.…”
Section: Helicity Induction On Optically Inactive Polyacetylenesmentioning
confidence: 93%
“…In the presence of bases such as NaOH and amines, (4-carboxyphenyl)-acetylene was rapidly and homogeneously polymerized with water-soluble rhodium complexes to yield high molecular weight poly-16 in high yields. 25 The obtained sodium salt of poly-16 also formed a predominantly one-handed helical structure with natural amino acids in water, and the complexes showed an ICD in the UV-visible region. However, this polymer is not sensitive to amino acids and other important chiral biomolecules in the fields of biology and medicine.…”
Section: Helicity Induction On Optically Inactive Polyacetylenesmentioning
confidence: 93%
“…The complexes form supramolecular assemblies with controlled helicity through electrostatic and hydrogen-bonding interactions in water. [23,50] For instance, the assay of 19 of the common free l-amino acids produced the ICDs of 9 e with the same Cotton effect signs, demonstrating that the polyelectrolyte functions as the first powerful chirality-sensing probe in water. This concept, that is, the use of a chromophoric dynamic helical polyelectrolyte, is promising for the construction of a specific sensory system for a target biomolecule by tuning the functional group of the polyelectrolyte.…”
Section: Chirality Sensing In Water By Helical Polyelectrolytesmentioning
confidence: 94%
“…We previously reported that macromolecular helicity could be induced on optically inactive, stereoregular poly(phenylacetylene)s bearing a variety of functional groups, such as carboxy, [23][24][25][26] boronate, 27,28 amino, 29,30 and phosphonate groups. 31 These poly(phenylacetylene)s form a predominantly one-handed helix upon complexation with optically active compounds capable of interacting with these functional groups and thus exhibit a characteristic induced circular dichroism (ICD) in the ultraviolet-visible region of the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%